2012
DOI: 10.1038/onc.2012.355
|View full text |Cite
|
Sign up to set email alerts
|

Mer or Axl receptor tyrosine kinase inhibition promotes apoptosis, blocks growth and enhances chemosensitivity of human non-small cell lung cancer

Abstract: Non-small cell lung cancer (NSCLC) is a prevalent and devastating disease that claims more lives than breast, prostate, colon, and pancreatic cancers combined. Current research suggests that standard chemotherapy regimens have been optimized to maximal efficiency. Promising new treatment strategies involve novel agents targeting molecular aberrations present in subsets of NSCLC. We evaluated 88 human NSCLC tumors of diverse histology and identified Mer and Axl as receptor tyrosine kinases (RTKs) overexpressed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
225
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(246 citation statements)
references
References 60 publications
20
225
0
1
Order By: Relevance
“…Among them, AXL expression was affected, indicating a potential interaction between hnRNP A2/B1 and AXL. Similar to the results reported by Linger et al (26), the current study revealed that positive expression of AXL was significantly higher in lung tumors than in paracancerous lung tissues. Additional investigation of clinical data indicated that AXL is highly associated with the prognosis of lung cancer, using univariate (but not multivariate) Cox regression models.…”
Section: Discussionsupporting
confidence: 81%
“…Among them, AXL expression was affected, indicating a potential interaction between hnRNP A2/B1 and AXL. Similar to the results reported by Linger et al (26), the current study revealed that positive expression of AXL was significantly higher in lung tumors than in paracancerous lung tissues. Additional investigation of clinical data indicated that AXL is highly associated with the prognosis of lung cancer, using univariate (but not multivariate) Cox regression models.…”
Section: Discussionsupporting
confidence: 81%
“…39,40 A more recent example is the receptor tyrosine kinase Axl, which has recently been shown to have a significant role in the malignant behavior of IBC cells 16 and has been previously revealed to block the induction of apoptosis through Akt and Bcl-xL. 41 However, our study is the first (to our knowledge) to directly address the molecular mechanisms that allow IBC cell survival in the context of ECM detachment. In addition, our findings suggest that targeting Bim-EL in a manner that promotes mitochondrial localization may be effective in the elimination of ECMdetached IBC cells.…”
Section: Discussionmentioning
confidence: 92%
“…25 To determine the differentially expressed genes, cuffdiff (with false-discovery rate ,0.001, fold-change . 18 Clonal populations of REH and 697 shMer cells were isolated by fluorescence-assisted single-cell sorting.…”
Section: Rna-seq and Data Analysismentioning
confidence: 99%
“…13 Transgenic Mer expression in mice results in the development of Tcell and biphenotypic lymphoblastic leukemia and lymphoma. 14 Mer activates antiapoptotic signaling proteins, including AKT and ERK1/2, [15][16][17] and promotes tumorigenic phenotypes in several other tumor types, including non-small-cell lung cancer, 18 melanoma, 19 and acute myeloid leukemia. 20 Here, we present data demonstrating increased Mer protein in E2A-PBX1…”
Section: 6mentioning
confidence: 99%